Mediastinal ectopic thyroid tissue, an imitator of an enlarged lymph node with metastatic pulmonary neoplasia. Issue 12 (7th September 2021) - Tsai, Alan; Rafferty, William; Ren, Shuyue
Abstract: The prevalence of ectopic thyroid tissue, based on autopsy studies, is between 7% and 10%, but there are rare cases reported in the thoracic region. Here, we encountered a case of thoracic ectopic thyroid tissue presenting as a presumed enlarged mediastinal lymph node. A 50‐year‐old female with a history of lung adenocarcinoma, status post resection, presented with complaints of headache, dizziness, and nausea. Magnetic resonance imaging found two brain lesions consistent with metastasis. Computed tomography scan showed enlarged mediastinal lymph nodes and thyroid nodules. Fine‐needle aspiration (FNA) of one thyroid nodule was positive for papillary thyroid carcinoma. FNA of the mediastinal lymph nodes were negative for metastatic carcinoma but revealed thyroid tissue in the 2.9 × 1.6 cm presumed 2 L lymph node. The morphological features and immunohistochemical stains confirmed thyroid tissue, and there were no cytological features of thyroid carcinoma. In patients with a history of a pulmonary tumor (such as adenocarcinoma, low‐grade neuroendocrine tumor), ectopic thyroid tissue, although a rare event, could represent a pitfall in the cytologic evaluation of mediastinal lymph nodes aspirates obtained from staging procedures. Careful morphologic examination with a panel of immunohistochemical studies are useful in making the correct diagnosis, leading to appropriate patient management.